Formulation of Vermicelli Mixed Corn and Rice Flour with Additional Carrageenan and Its Economic Value - Moh Saeri; Joko Mariyono; Evy Latifah; Aniswatul Khamidah; Ita Yustina; Sugiono Sugiono; Khojin Supriadi; Herman Subagio; Sri Satya Antarlina (International Journal of Food Science)
The study was aimed at obtaining a vermicelli formulation on a mixture of corn and rice flour, adding carrageenan and its economic analysis. The experiment applied a 2-factorial randomized block design, where factor 1 was a mixture of corn and rice flour (5 levels) and factor 2 was carrageenan concentration (5 levels), repeated three times. The data were analyzed using ANOVA provided in SPSS. When there were significant differences, the analysis proceeded with DMRT at a level of 5% to see differences among treatments. The results show that the higher the corn flour and carrageenan concentration, the higher the vermicelli’s ash and fat content. The formulation produces wet vermicelli with a good appearance. The production of vermicelli uses an extruder method. The selected vermicelli formulation was a mixture of 25% corn flour with 75% rice flour and the addition of 0.6% carrageenan. The characteristics of the wet vermicelli are moisture content of 42.84%, ash content of 0.21% on a wet basis (wb), and fat content of 0.43% wb. The organoleptic test of vermicelli was color 3.9 (liked), aroma 3.6 (liked), texture 2.6 (quite soft), taste 3.7 (liked), and general appearance 3.5 (liked). Economically, making vermicelli made of corn and rice flour is profitable because the R/C ratio value is greater than one, which is 2.27. The resulting wet vermicelli resembles wet noodles, large in size and yellow in color, so it can be recommended as gluten-free noodles, suitable for consumption by people with gluten allergies.